Improvement of Pulse-Width Modulation Algorithm for Thermal Plant Control - Roman Fedoryshyn; Sviatoslav Klos; Volodymyr Savytskyi; Sergiy Kril (Energy Engineering and Control Systems)
The results of the pulse-width modulation algorithms analysis are presented in the paper. The following two algorithms are analyzed: pulse-width modulator (PWM) based on the sawtooth waveform generator and PWM based on an integrator and a switch element. Mathematical formulae for designing the tuning parameters of PWM algorithms are presented. An improved PWM algorithm is suggested for a programmable logic controller (PLC) operating with integer variables without a filter of the input signal. The improved algorithm provides elimination of the influence of the input signal’s noise on the PLC output signal. PLC output relay contact bouncing is eliminated by means of the improved algorithm. The reliability of PLC is improved and the operation time of PLC output relay contact is prolonged thanks to the improved PWM algorithm. The example of PWM application in an automatic controller for controlling a thermal plant is presented. The advantages of the improved PWM algorithm application are demonstrated. The technique for PWM pulses period defining with taking into account the dynamical properties of the controlled plant is presented.